Including the excluded: Sense-making and job crafting as drivers of dialogical change management in Italian universities for refugees' inclusion - Federico Ceschel; Plinio Limata; Lucia Marchegiani (Administrative Sciences, 2023)
Higher Education Institutions (HEIs) are increasingly called to substantiate their impact on society in terms of inclusivity and social sustainability, as prioritized in the pursuit of the "Third Mission" (TM). Today, HEIs are confronted with the demand to ensure refugees' inclusivity. However, how administrative and teaching staff enact such change within the organization to match the TM goals is under-investigated. This study explores the adoption of the European Qualification Passport for Refugees (EQPR) as an instrument for universities to pursue the TM in Italy. By adopting a theoretical sense-making approach, we find that the individual role of the staff in fostering organizational change depends on the adopted "emergent" approach to change and on internal factors, such as individual perceptions and experiences. This study contributes to the literature by showing contradictory aspects of the HEIs' pursuit of the TM. It sheds light on the interplay between different dimensions and grounded processes of sense-making.
Keywords: 350; European Qualification Passport for Refugees (EQPR); higher education institutions; job-crafting; organizational change; sense-making; Third Mission